Risk-assessment algorithm and recommendations for venous thromboembolism prophylaxis in medical patients - T Rocha, Ana (Dove Medical Press, 2007)
The risk for venous thromboembolism (VTE) in medical patients is high, but risk assessment is rarely performed because there is not yet a good method to identify candidates for prophylaxis. PURPOSE: To perform a systematic review about VTE risk factors (RFs) in hospitalized medical patients and generate recommendations (RECs) for prophylaxis that can be implemented into practice. DATA SOURCES: A multidisciplinary group of experts from 12 Brazilian Medical Societies searched MEDLINE, Cochrane, and LILACS. STUDY SELECTION: Two experts independently classified the evidence for each RF by its scientific quality in a standardized manner. A risk-assessment algorithm was created based on the results of the review. DATA SYNTHESIS: Several VTE RFs have enough evidence to support RECs for prophylaxis in hospitalized medical patients (eg, increasing age, heart failure, and stroke). Other factors are considered adjuncts of risk (eg, varices, obesity, and infections). According to the algorithm, hospitalized medical patients ≥40 years-old with decreased mobility, and ≥1 RFs should receive chemoprophylaxis with heparin, provided they don’t have contraindications. High prophylactic doses of unfractionated heparin or low-molecular-weight-heparin must be administered and maintained for 6–14 days. CONCLUSIONS: A multidisciplinary group generated evidence-based RECs and an easy-to-use algorithm to facilitate VTE prophylaxis in medical patients.